Judges. (Blackwell Bible Commentaries), David M. Gunn : book review - Nel, Philip Johannes (Old Testament essays, 2006)
Extracted from text ... Gunn, David M 2005. Judges. (Blackwell Bible Commentaries). Oxford: Blackwell. Xiv - 329 pages. Paperback. 17.99. ISBN 0-631-22252-9. The Blackwell Commentary series seeks to expose the reader to the reception history of Biblical texts. The decision to allocate the book Judges to David Gunn could not have been a better choice, bearing in mind his work on biblical narrative material and his keen interest in modes of interpretation. No wonder he found it hard to limit the scale of the book to its present size. Many would say such a project is too ambitious, for one would never be able ..